Perceived Barriers Regarding Pain Management in Critically Ill Patients among Nurses Working in Tertiary Hospital - Aryal, Neelu; Shrestha, Kamna; Sapkota, Devi Kumari; Raskoti, Pushpa (Journal of College of Medical Sciences-Nepal, 2025)
Background Pain is a significant concern and a primary reason people seek medical care, particularly in critical care settings. Patients should not endure unmanaged pain, especially when solutions are available, as every individual has the right to optimal pain assessment and management. This study aimed to assess perceived barriers regarding pain management among nurses working with critically ill patients at Bharatpur Hospital. Methods A cross-sectional descriptive research design was utilized, involving 88 staff members from the ICU, PICU, and ER. Data were collected between June 16 and June 29 using a non-probability purposive sampling technique. A self-administered, structured questionnaire with five-point Likert scale facilitated data collection, which was subsequently analyzed using SPSS version 20. Results The study findings revealed that key barriers identified included nurses’ workload (3.47±1.01), financial constraints of patients (3.06±0.11), inadequate staffing (3.06±0.91), and time constraints (3.01±0.91). The study concluded that barriers related to medical staff are more prevalent among nurses than other types of barriers. Conclusions Thus, it is crucial to emphasize the necessity of focused interventions, such improving time management techniques, optimizing workforce numbers, and addressing financial support mechanisms, in order to raise the general efficacy and efficiency of healthcare delivery systems.